Ventilator-induced lung injury and acute respiratory distress syndrome: a basic science review - Ronchi, Carlos Fernando [UNESP]; Klefens, Susiane de Oliveira [UNESP]; Ferreira, Ana Lúcia dos Anjos [UNESP]; Ronchi, Carolina Bragiola Berchieri [UNESP]; Carpi, Mário Ferreira [UNESP]; Moraes, Marcos Aurélio [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Gimenes, Camila; Arca, Eduardo Aguilar; Fioretto, José Roberto [UNESP] (OMICS International, 2012)
Acute respiratory distress syndrome is the most severe manifestation of acute lung injury and it is associated with high mortality rate. Despite better understanding of ARDS pathophysiology, its mechanism is still unclear. Mechanical ventilation is the main ARDS supportive treatment. However, mechanical ventilation is a non-physiologic process and complications are associated with its application. Mechanical ventilation may induce lung injury, referred to as ventilator-induced lung injury. Frequently, VILI is related to macroscopic injuries associated with alveolar rupture. The present article is a review of the literature on ventilator-induced lung injury in acute respiratory distress syndrome. Animal and human studies were reviewed. We mainly selected publications in the past 5 years, but did not exclude commonly referenced and highly regarded older publications.
Keywords: Ventilator-induced lung injury; Mechanical ventilation; Acute lung injury; Acute respiratory distress syndrome